La educación de jóvenes y adultos frente al desafío de los movimientos sociales emergentes en Argentina - María Teresa Sirvent (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
This article situates popular and youth education in Argentina in its historical context, with relation to the social movements, from the end of the military dictatorship in 1973 up to the present day. It analyses the theoretical difficulties in understanding the limitations underlying social participation, resulting from the period of the dictatorship, as well as the challenges and contradictions of the present moment.